2018
DOI: 10.3389/fphar.2018.01413
|View full text |Cite
|
Sign up to set email alerts
|

β-Elemene Synergizes With Gefitinib to Inhibit Stem-Like Phenotypes and Progression of Lung Cancer via Down-Regulating EZH2

Abstract: The inhibitors for EGF receptor tyrosine kinase (EGFR-TKIs) such as gefitinib have been used as a standard treatment for non-small cell lung cancer (NSCLC), but the increasingly occurrence of drug resistance, the associated adverse effects and the enrichment of cancer stem cells significantly impedes its clinical application. β-elemene is a natural sesquiterpene with potent anti-cancer ability, and also it is renowned for its plant-origin, safety and the additive effect with traditional therapies, which prompt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…The results showed that, compared with either single agent, the combination of ATF 24 -PEG-Lipo-β-E and DDP caused significant cell cycle arrest at the G2/M phase ( Figure 5F and 5I ). Consistent with this finding, the colony-forming ability of the KU-19-19 cells was significantly reduced by co-treatment of ATF 24 -PEG-Lipo-β-E and DDP, compared with those observed following treatment with either single agent treatment ( Figure 5G ) 46 . Together, the results indicated that the co-treatment of ATF 24 -PEG-Lipo-β-E and DDP had a synergistic effect in reducing cellular viability and proliferation in bladder cancer.…”
Section: Resultssupporting
confidence: 80%
“…The results showed that, compared with either single agent, the combination of ATF 24 -PEG-Lipo-β-E and DDP caused significant cell cycle arrest at the G2/M phase ( Figure 5F and 5I ). Consistent with this finding, the colony-forming ability of the KU-19-19 cells was significantly reduced by co-treatment of ATF 24 -PEG-Lipo-β-E and DDP, compared with those observed following treatment with either single agent treatment ( Figure 5G ) 46 . Together, the results indicated that the co-treatment of ATF 24 -PEG-Lipo-β-E and DDP had a synergistic effect in reducing cellular viability and proliferation in bladder cancer.…”
Section: Resultssupporting
confidence: 80%
“…Considering that the epithelial-mesenchymal transition (EMT) and minor subpopulations of cancer stem cells (CSCs) have been reported to associated with acquired resistance of gefitinib in NSCLC, 23,24 we used qRT-PCR to study the effect of circSETD3 on the expression of EMT markers (vimentin, N-cadherin, E-cadherin, and keratin 18) and stemness-related markers (CD133, OCT4, NANOG, and SOX2). Our results showed that there were no significant differences in these markers after circSETD3-overexpression plasmid (OE-circSETD3) and circSETD3-short hairpin RNA (shRNA) (sh-circSETD3) (Figure S2), which indicates that the function of circSETD3 in gefitinib resistance was irrelevant with EMT or stem cell properties in NSCLC.…”
Section: Upregulated Circsetd3 Reduces Sensitivity To Gefitinib In Nsmentioning
confidence: 99%
“…β-elemene is a bioactive compound isolated from the traditional Chinese medicinal herb Curcuma wenyujin (38). It exerts a wide range of antitumor activities and has been approved in China to treat a wide spectrum of cancers including brain (9), breast (39), ovarian (40), gastric (41), hepatic (42) and lung cancers (43). A meta-analysis, including 46 clinical controlled trials with 2,992 patients, evaluated the efficacy and safety of β-elemene in treating malignant pleural effusion, and showed that β-elemene significantly improved the overall response rate in controlling malignant pleural effusion [risk ratio (RR) = 1.16; 95% CI: 1.08–1.23; P < 0.05) (14).…”
Section: Discussionmentioning
confidence: 99%